The impact of public basic research on industrial innovation: Evidence from the pharmaceutical industry - Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
While most economists believe that public scientific research fuels industry innovation and economic growth, systematic evidence supporting this relationship is surprisingly limited. In a recent study, Acemoglu and Linn (2004) identified market size as a significant driver of drug innovation in the pharmaceutical industry, but they did not find any evidence supporting science-driven innovation from publicly funded research. This paper uses new data on biomedical research investments by the U.S. National Institutes of Health (NIH) to examine the contribution of public research to pharmaceutical innovation. The empirical analysis finds that both market size and NIH funded basic research have economically and statistically significant effects on the entry of new drugs with the contribution of public basic research coming in the earliest stage of pharmaceutical drug discovery. The analysis also finds a positive return to public investment in basic biomedical research.
Keywords: O31; O32; L65; H51; 330; R&D; NIH; social return; biomedical; research lags; public science; new molecular entities